2022
DOI: 10.1155/2022/2520695
|View full text |Cite
|
Sign up to set email alerts
|

The Positive and Negative Effects of Calcium Supplementation on Mortality in Septic ICU Patients Depend on Disease Severity: A Retrospective Study from the MIMIC-III

Abstract: Background. Calcium administration in septic patients with hypocalcemia is a controversial issue. The present study preliminarily investigated the effects of calcium supplementation on the length of hospitalization and mortality in septic ICU patients with different severities of hypocalcemia and disease. Method. A total of 5761 eligible septic patients, including 2689 who received calcium supplementation and 3072 who did not receive calcium supplementation, were extracted from the Medical Information Mart for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
2
8
0
1
Order By: Relevance
“…This suggests that mild hypocalcemia may be protective against sepsis. A retrospective study [27] found that mild hypocalcemia may have a protective effect in septic patients, and calcium supplementation may have both positive and negative effects on mortality depending on the severity of the disease. Aberegg also suggested that low iCa levels may be protective in critically ill patients, whereas attempts to correct low levels may be harmful [6] .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that mild hypocalcemia may be protective against sepsis. A retrospective study [27] found that mild hypocalcemia may have a protective effect in septic patients, and calcium supplementation may have both positive and negative effects on mortality depending on the severity of the disease. Aberegg also suggested that low iCa levels may be protective in critically ill patients, whereas attempts to correct low levels may be harmful [6] .…”
Section: Discussionmentioning
confidence: 99%
“…In a subset of this cohort of sepsis patients, He et al . [29] found a longer ICU and hospital length of stay (LOS) after calcium supplementation was given. Furthermore, a higher 90-day mortality was found following calcium administration in patients with iCa 1.01–1.20 mmol/l, while in patients with iCa levels below 1.01 mmol/l, it might be beneficial [29].…”
Section: Management Of Hypocalcaemia In the Icumentioning
confidence: 99%
“…Despite the absence of an evidence-based threshold for calcium supplementation and its inefficacy in restoring serum calcium levels, as well as the transient nature of hypocalcaemia, calcium administration occurs frequently in the ICU. In 18-79% of the ICU patients included in observational studies, calcium was administered [7,25,29,32,52,53] (M. Melchers, H.P.F.X. Moonen, T.S.…”
Section: Management Of Hypocalcaemia In the Icumentioning
confidence: 99%
See 2 more Smart Citations